Identification Causes Leaf Spot Disease in Cempaka (Magnolia elegans (Blume.) H.Keng) Seedling and Its Control Techniques - Irawan, Arif Irawan; Anggraeni, Illa Anggraeni; Margaretta, Margaretta Christita (Forestry Department, University of Muhammadiyah Makassar, 2015)
This research purposes to identify the pathogen causing leaf spot in cempaka seedling and its control technique. Identify cause of disease is necessary to know precise technique control. Identification of disease was conducted in macroscopic appearances and microscopically to determine pathogens. Identification is done by using the determination key of fungi. The results showed that the early signs of leaf spot disease on cempaka seedlings in the nursery are streaks or spots on the leaf surface with distinct boundaries. Leaf spots are formed generally brown surrounded by darker boundaries. The result shows leaf spot disease on cempaka seedling was caused by fungal pathogen Colletotrichum sp. Techniques for controlling the disease can be done by isolating the infected seeds, reducing the intensity of canopy, and using the appropriate fungicides.